PERCEPTION OF NURSES IN DECISION-MAKING PROCESS IN PALLIATIVE CARE FOR PATIENTS WITH CANCER IN PUBLIC HEALTH CENTERS - Atsarina Fauzan; Sri Setiyarini; Christantie Effendy; Martina Sinta Kristanti (Belitung Raya Foundation, Indonesia, 2019)
Background: Nurses have a key role in promoting patients’ involvement in decision-making process of palliative care to improve their dignity and satisfaction. However, there is a dearth of studies exploring this involvement, especially in public health centers in Indonesia. Objective: This study aimed to explore the perception of nurses in decision-making process and to understand what type of decision-making made by health care providers in palliative care. Methods: This was a descriptive explorative study with qualitative approach. Participants were selected using purposive and snowball sampling. Data were collected using Focus Group Discussion (FGD) and in-depth interview. Content analysis method by inductive approach was used for data analysis. Consolidated criteria for reporting qualitative research (COREQ) was also used. Results: Eight themes emerged in this study, namely: (1) Collecting information about patients’ current physiological condition, (2) Creating alternative strategies according to the patients’ current physiological condition, (3) Establishing implementation type to be performed, (4) Providing information to the patients, (5) Discussing decision-making between patients and family, (6) Choosing/rejecting an action by patients, (7) Performing selected actions, and (8) Evaluating action. Three points that are different from the existing theory were: (i) there was a discussion between patients and family, (ii) the absence of the process of collecting information after a patient rejects to act, and (iii) there were three types of decision-making: paternalistic, shared, and informed decision-making. Conclusion: This study serves as an input for nurses to pay more attention in decision-making process in palliative care in patients with cancer, and to encourage patients to give contribution in decision-making as part of shared decision-making.